Composite photocatalyst, manufacturing method and application
By combining triazine-based covalent organic framework compounds with cadmium sulfide to form a composite photocatalyst with Z-type heterojunction structure, the problems of band gap matching and poor interface contact of traditional heterojunction photocatalysts are solved, and efficient photocatalytic decomposition of water hydrogen analysis is achieved.
Patent Information
- Application Number
- CN202311638575.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2025-06-03
AI Technical Summary
Traditional heterojunctions composed of two inorganic semiconductors have problems such as poor band gap matching and poor interface contact in the field of photocatalysis, resulting in relatively low photocatalytic efficiency.
By combining triazine-based covalent organic framework compound (TFPT-DHTH-COF) with cadmium sulfide (CdS), a covalent organic framework/cadmium sulfide composite photocatalyst is formed, and the carrier transfer efficiency is improved using the Z-type heterojunction structure.
The yield of photocatalytic decomposition of water hydrogen analysis by photocatalysts is significantly improved, the photocatalytic efficiency is improved, and excellent photostability is demonstrated.
Smart Images

Figure CN120079443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalysis, and specifically relates to a composite photocatalyst, a manufacturing method of the composite photocatalyst, and an application of photocatalytic water splitting for hydrogen evolution. Background Art
[0002] Splitting water into hydrogen using solar energy, in which solar energy is converted into chemical energy and stored in chemical bonds during this process, is a very promising technology that can produce clean and sustainable energy to replace traditional fossil fuels. Efficient semiconductor photocatalysts play a crucial role in this process, and they need to have characteristics such as a wide light absorption bandwidth, efficient carrier separation and transport, effective surface reactions, and long-term stability. Composite heterojunction photocatalysts have received extensive attention in the field of solar hydrogen production. Since the redox reaction occurs on two different tandem structures, the carrier transfer efficiency can reach nearly 100%. For example, heterojunctions based on TiO 2 and various metal sulfides exhibit higher photocatalytic hydrogen production efficiency. However, traditional heterojunctions composed of two inorganic semiconductors still have problems such as poor bandgap matching and poor interfacial contact, resulting in relatively low photocatalytic efficiency. Summary of the Invention
[0003] In one aspect, the present invention provides a manufacturing method of a composite photocatalyst, which includes adding a prepolymer 1,3,5-tris(4-formylphenyl)triazine (TFPT), 2,5-bis(3-hydroxypropoxy) isophthalohydrazone (DHTH), and glacial acetic acid solution to a mixed solvent of mesitylene and dioxane to form a prepolymer mixture. Freezing the prepolymer mixture in liquid nitrogen, sealing it under vacuum, filling it with nitrogen, and reacting it at a temperature of 90 - 120 °C for 60 - 80 hours to obtain a triazine-based covalent organic framework compound (TFPT-DHTH-COF). Dispersing the triazine-based covalent organic framework compound (TFPT-DHTH-COF) and cadmium acetate dihydrate in deionized water. Adding dimethylformamide solvent and thiourea and stirring evenly to grow cadmium sulfide crystals on the surface of the triazine-based covalent organic framework compound to form a suspension. Reacting the suspension at a temperature of 150 - 180 °C for 10 - 15 hours to obtain a covalent organic framework / cadmium sulfide composite photocatalyst (CdS / TFPT-DHTH-COF).
[0004] Preferably, the molar ratio of 1,3,5-tris(4-formylphenyl)-1,3,5-triazine to 2,5-bis(3-hydroxypropoxy) isophthalohydrazone is 2:3. The volume ratio of mesitylene to dioxane is 7:3. The volume ratio of glacial acetic acid to the mixed solvent of mesitylene and dioxane is 10:1. The mass ratio between the triazine-based covalent organic framework compound and cadmium acetate dihydrate is 1:(9 - 90). The volume ratio of deionized water to dimethylformamide is 1:6. The mass ratio between cadmium acetate dihydrate and thiourea is 3:5.
[0005] According to another aspect, the present invention provides a covalent organic framework compound / cadmium sulfide composite photocatalyst manufactured by the method described above.
[0006] According to yet another aspect, the present invention provides the application of the covalent organic framework compound / cadmium sulfide composite photocatalyst in photocatalytic hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] The following describes various embodiments of the present invention with reference to the drawings, where:
[0008] Figure 1 is a flowchart of a method for manufacturing a covalent organic framework compound / cadmium sulfide composite photocatalyst according to an embodiment of the present invention;
[0009] Figure 2A and 2B respectively show the synthesis process of TFPT-DHTH-COF and the synthesis process of CdS / TFPT-DHTH-COF composite materials according to an embodiment of the present invention, as well as schematic diagrams of the chemical formulas of the corresponding materials;
[0010] Figure 3 shows the comprehensive PXRD patterns of CdS and CdS / TFPT-DHTH-COF composite materials with different CdS contents;
[0011] Figure 4A and 4B respectively show the transmission electron microscope (TEM) image and high-resolution transmission electron microscope (HRTEM) image of the covalent organic framework compound / cadmium sulfide composite material;
[0012] Figure 5 shows the ultraviolet-visible DRS spectra of CdS, TFPT-DHTH-COF, and CdS / TFPT-DHTH-COF20;
[0013] Figure 6The photocatalytic hydrogen evolution rates of CdS, TFPT-DHTH-COF, and CdS / TFPT-DHTH-COF photocatalysts are shown (10 mg of the catalyst is dissolved in 100 mL of deionized water, 3 wt% Pt, 0.1 M ascorbic acid, AM 1.5G 300W Xe lamp);
[0014] Figure 7 The hydrogen evolution time course of CdS / TFPT-DHTH-COF20 for five consecutive cycles is shown to test the stability. Detailed implementation manners
[0015] It can be understood that, in addition to the described exemplary embodiments, the components of the embodiments generally described and shown in the accompanying drawings herein can be arranged and designed in various different settings. Therefore, the exemplary embodiments represented in conjunction with the accompanying drawings and the following more detailed description are only representatives of the exemplary embodiments and do not limit the scope of the embodiments claimed.
[0016] References in this specification to "one embodiment", "another embodiment", or "an embodiment" (or similar terms) are intended to mean that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the phrases "in one embodiment" or "in an embodiment" and the like that appear throughout this specification may refer to the same embodiment or to different embodiments that are combined together.
[0017] In addition, the described features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. In the following description, numerous specific details are provided to provide a thorough understanding of the embodiments. However, those skilled in the relevant art will realize that various embodiments can be practiced without one or more of the specific details or by using other methods, components, materials, etc. In other cases, some or all of the known structures, materials, or operations may be omitted.
[0018] The present invention provides a method for manufacturing a composite photocatalyst. As Figure 1 shown, the method 100 for manufacturing a composite photocatalyst according to an embodiment of the present invention includes, in step 110, adding the prepolymers 1,3,5-tris(4-formylphenyl)triazine (TFPT) and 2,5-bis(3-hydroxypropoxy) isophthalohydrazone (DHTH) to a mixed solvent of mesitylene and dioxane, mixing evenly and then adding an acetic acid solution to form a prepolymer mixture. In a specific example, the molar ratio of 1,3,5-tris(4-formylphenyl)triazine and 2,5-bis(3-hydroxypropoxy) isophthalohydrazone (DHTH) is 2:3; the volume ratio of the solvents mesitylene and dioxane is 7:3; the volume ratio of acetic acid to the mixed solvent is 10:1, the concentration of the prepolymer relative to the mixed solvent is 0.01 - 0.05 mmol / mL, and the concentration of acetic acid is 6 mol / L.
[0019] In step 120, the pre-polymer mixture is rapidly frozen in liquid nitrogen and subjected to a cyclic operation of filling with nitrogen. Subsequently, after sealing under vacuum, it is reacted at a temperature of 90 - 120 °C for 60 - 80 hours to obtain a triazine-based covalent organic framework compound (TFPT-DHTH-COF).
[0020] In step 130, the triazine-based covalent organic framework compound and cadmium acetate dihydrate are dispersed in deionized water and stirred evenly by ultrasonic waves. The mass ratio between the triazine-based covalent organic framework compound and cadmium acetate dihydrate can be 1:(9 - 90). Preferably, the mass ratio of the triazine-based covalent organic framework compound to cadmium acetate dihydrate is 2:45, and the concentration of cadmium acetate dihydrate in deionized water is 45 mg / mL.
[0021] In step 140, N,N-dimethylformamide solvent and thiourea are added and stirred evenly to allow cadmium sulfide crystals to grow on the surface of the triazine-based covalent organic framework compound and form a suspension.
[0022] In step 150, the suspension is reacted at a temperature of 150 - 180 °C for 10 - 15 hours. Preferably, the suspension is reacted at a temperature of 160 °C for 12 hours. The solid product is collected by filtration and, after drying, a covalent organic framework / cadmium sulfide composite photocatalyst is obtained.
[0023] In one embodiment, the present invention provides a covalent organic framework compound / cadmium sulfide composite photocatalyst according to method 100.
[0024] In one embodiment, the present invention also provides the application of the above-mentioned covalent organic framework compound / cadmium sulfide composite photocatalyst in photocatalytic hydrogen evolution.
[0025] The following examples describe the preparation and manufacturing methods of the relevant materials according to the present invention.
[0026] Example 1
[0027] The preparation of TFPT-DHTH-COF is as follows:
[0028] (1) Place 1,3,5-tris(4-formylphenyl)-1,3,5-triazine (17.3 mg, 0.044 mmol) and 2,5-bis(3-hydroxypropoxy) isophthaloyl dihydrazone (22.6 mg, 0.066 mmol) into a 10 mL ampoule. Then add 0.7 mL of mesitylene and 0.3 mL of dioxane. The mixture is ultrasonically stirred for 10 minutes.
[0029] (2) After ultrasonic stirring to evenly disperse the solid, add 0.1 mL of 6 M glacial acetic acid solution. Then freeze with liquid nitrogen, evacuate, and introduce nitrogen. Repeat this step three times. Then seal the ampoule under vacuum conditions.
[0030] (3) After returning to room temperature, place it in an oven at 120 °C for 3 days. After the reaction is completed, cool to room temperature. Filter to collect the powder, wash it with ethanol and acetone, and place it in a Soxhlet extractor. Then extract with tetrahydrofuran, methanol, dichloromethane, and acetone for 24 hours successively, and dry under vacuum to obtain the yellow powder of TFPT-DHTH-COF composite material. Its formation process and chemical formula are as Figure 2A shown.
[0031] Example 2
[0032] The preparation of the covalent organic framework compound / cadmium sulfide composite material is as follows:
[0033] (1) Place the powder of TFPT-DHTH-COF obtained according to Example 1 in a mortar and grind it for 10 minutes. After fully grinding, weigh 20 mg of the powder and add 450 mg of cadmium acetate dihydrate to 10 mL of deionized water. Ultrasonically stir for 30 minutes to mix evenly.
[0034] (2) Slowly add 60 mL of N,N-dimethylformamide (DMF) to the above solution. Then add 700 mg of thiourea and stir for 30 minutes to mix evenly. Subsequently, transfer it to a 100 mL reaction kettle and react at 160 °C for 12 h.
[0035] (3) After the reaction is completed, cool to room temperature. The reaction product is collected by filtration, washed several times with deionized water and methanol, and then placed in a vacuum drying oven at 70 °C to dry overnight to obtain the CdS / TFPT-DHTH-COF covalent organic framework compound / cadmium sulfide composite material. Its formation process and chemical formula are as Figure 2B shown.
[0036] By adding different amounts of TFPT-DHTH-COF during the preparation of the composite material, covalent organic framework compound / CdS composites with different contents of CdS / TFPT-DHTH-COFx (x = 10, 20, and 30, representing 10 mg, 20 mg, and 30 mg of TFPT-DHTH-COF respectively) can be obtained. For example, CdS / TFPT-DHTH-COF10 is a covalent organic framework compound / CdS composite containing 10 mg of TFPT-DHTH-COF. CdS / TFPT-DHTH-COF20 is a covalent organic framework compound / CdS composite containing 20 mg of TFPT-DHTH-COF. CdS / TFPT-DHTH-COF30 is a covalent organic framework compound / CdS composite containing 30 mg of TFPT-DHTH-COF.
[0037] Example 3
[0038] The prepared covalent organic framework compound / CdS composite photocatalyst was used for photocatalytic water splitting for hydrogen evolution applications:
[0039] Disperse 10 mg of the photocatalyst in 100 mL of pure water, then add 1.76 g of ascorbic acid as a sacrificial reagent. After mixing evenly by ultrasonic stirring for 15 minutes, add 3 wt% Pt as a cocatalyst. Connect the reactor to the photocatalytic evaluation device and evacuate it, and then start the photocatalytic reaction under xenon lamp irradiation. The hydrogen obtained was analyzed by gas chromatography. The efficiency of adding covalent organic framework compound / CdS composite photocatalysts with different masses is as Figure 6 shown. As the mass of the covalent organic framework compound increases, the hydrogen production efficiency of the composite photocatalyst first increases and then decreases, and there is an optimal composite ratio.
[0040] Example 4
[0041] Characterization of Covalent Organic Framework Compound / Cadmium Sulfide Composite
[0042] The morphology of the newly prepared photocatalyst was examined using a transmission electron microscope (TEM). Figure 4A The enlarged TEM image of the CdS / TFPT-DHTH-COF composite material shown indicates that CdS nanoparticles are firmly attached to the surface of TFPT-DHTH-COF. Figure 4B The HRTEM image shown indicates that lattice fringes with a spacing of 0.34 nm are presented on the surface nanocrystals corresponding to the (002) plane of CdS.
[0043] The crystal structure was further investigated using powder X-ray diffraction (PXRD). As Figure 3As shown, the diffraction peaks in the PXRD pattern of the CdS / TFPT-DHTH-COF composite material are in good agreement with the typical hexagonal phase of CdS nanoparticles (JCPDS: 41-1409). Due to the low content of TFPT-DHTH-COF, the PXRD pattern does not show obvious diffraction peaks of TFPT-DHTH-COF.
[0044] As Figure 5 shown, the optical properties of TFPT-DHTH-COF, CdS nanoparticles and their composite material CdS / TFPT-DHTH-COF20 presented by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) show that the CdS / TFPT-DHTH-COF20 composite material exhibits almost the same light absorption range as CdS nanoparticles, which means that the CdS in the composite material has a similar crystal structure and particle size to pure CdS nanoparticles. This is further confirmed by the Figure 3 PXRD pattern shown.
[0045] Using ascorbic acid as a sacrificial agent and Pt as a cocatalyst, the photocatalytic hydrogen evolution (PHE) rates of different photocatalysts were measured under simulated sunlight irradiation. As Figure 6 shown, TFPT-DHTH-COF and CdS show relatively poor PHE rates, which are 0.21 mmol h -1 g -1 and 4.57 mmol h -1 g -1 respectively. In contrast, the PHE rate of the CdS / TFPT-DHTH-COF composite material is significantly improved. Among different CdS / TFPT-DHTH-COF composite materials, the best PHE rate of CdS / TFPT-DHTH-COF20 is 15.75 mmol h -1 g -1 , which are 75 times and 3.4 times that of TFPT-DHTH-COF and CdS respectively. The significant enhancement of the photoactivity of the CdS / TFPT-DHTH-COFx composite material can be attributed to the formation of a Z-scheme heterojunction between CdS and TFPT-DHTH-COF.
[0046] To study the effect of the heterostructure on PHE generation, the PHE generation of different photocatalysts under monochromatic light irradiation at 365 nm and 520 nm was detected. Under 520 nm irradiation that can only excite CdS, the PHE hydrogen evolution rate of CdS / TFPT-DHTH-COF20 is only slightly higher than that of pure CdS nanoparticles ( Figure 6 ), and the increase is roughly consistent with the increase in absorption (light collection ability) at 520 nm ( Figure 5)。TFPT-DHTH-COF does not absorb light at 520 nm, so no PHE is generated. However, under irradiation with 365 nm monochromatic light that can simultaneously excite TFPT-DHTH-COF and CdS NPs, the PHE hydrogen evolution rate of CdS / TFPT-DHTH-COF20 (3.23 mmol h -1 g -1 ) is more than 3 times that of CdS (1.04 mmol h -1 g -1 ) and 83 times that of pure TFPT-DHTH-COF, far higher than the total hydrogen evolution rate of pure CdS NPs and pure TFPT-DHTH-COF. The formation of the Z-scheme heterojunction in the CdS / TFPT-DHTH-COF20 composite significantly improves PHE.
[0047] Under irradiation with 365 nm monochromatic light, the AQY value of CdS / TFPT-DHTH-COF20 is the highest, at 5.36%. The PHE stability of CdS / TFPT-DHTH-COF20 was studied by cyclic testing. The photocatalytic performance of CdS / TFPT-DHTH-COF20 remained almost unchanged after five runs (4 hours of light irradiation each time), demonstrating its excellent photo-stability ( Figure 6 )
[0048] The present invention provides a method for synthesizing and preparing a covalent organic framework compound / cadmium sulfide composite photocatalyst. The combination of the two materials in the obtained covalent organic framework compound / cadmium sulfide composite photocatalyst can not only enhance its visible light absorption ability but also enhance the separation and transport of photoexcited electrons. Therefore, an efficient composite photocatalyst can be prepared according to the method provided by the present invention.
[0049] Compared with the prior art, the present invention has the following remarkable advantages:
[0050] (1) For the composite material manufactured according to the method provided by the present invention, due to the aggregation of cadmium sulfide crystals on the surface of the covalent organic framework compound, a structure with a scaly surface is formed, which can enhance the light absorption ability of the composite material.
[0051] (2) The abundant and uniformly distributed nitrogen atoms on the covalent organic framework compound skeleton can firmly anchor cadmium sulfide nanocrystals through nitrogen-metal interactions, ensuring that the two can be tightly combined together to form a heterojunction, enabling photoexcited electrons to be transported between the two, thereby improving the separation of photo-generated electron-hole pairs and the photocatalytic efficiency.
[0052] (3) Compared with its component materials, the photocatalytic water splitting hydrogen evolution yield of the composite material manufactured according to the method provided by the present invention has been greatly improved, having potential application value.
[0053] The present invention has been presented for purposes of illustration and description, but is not intended to be exhaustive or limiting. The exemplary embodiments have been selected and described to explain the technical solutions and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the various embodiments of the present invention, which may include various modifications suitable for a specific intended use.
Claims
1. A method for manufacturing a composite photocatalyst, characterized in that, the method comprises: adding a prepolymer 1,3,5-tris(4-formylphenyl)triazine (TFPT), 2,5-bis(3-hydroxypropoxy)terephthalohydrazide (DHTH), and glacial acetic acid solution into a mesitylene and dioxane mixed solvent to form a prepolymer mixture; freezing the prepolymer mixture in liquid nitrogen, sealing it under vacuum, filling it with nitrogen, and reacting it at a temperature of 90 - 120 °C for 60 - 80 hours to obtain a triazine-based covalent organic framework compound (TFPT-DHTH-COF); dispersing the triazine-based covalent organic framework compound (TFPT-DHTH-COF) and cadmium acetate dihydrate in deionized water; adding dimethylformamide solvent and thiourea and stirring to mix evenly, enabling cadmium sulfide crystals to grow on the surface of the triazine-based covalent organic framework compound to form a suspension; reacting the suspension at a temperature of 150 - 180 °C for 10 - 15 hours to obtain a covalent organic framework / cadmium sulfide composite photocatalyst (CdS / TFPT-DHTH-COF).
2. The method according to claim 1, characterized in that, the molar ratio of the 1,3,5-tris(4-formylphenyl)triazine to the 2,5-bis(3-hydroxypropoxy)terephthalohydrazide is 2:
3.
3. The method according to claim 1, characterized in that, the volume ratio of the mesitylene to the dioxane is 7:
3.
4. The method according to claim 1, characterized in that, the volume ratio of the glacial acetic acid to the mesitylene and dioxane mixed solvent is 10:
1.
5. The method according to claim 1, characterized in that, the mass ratio between the triazine-based covalent organic framework compound and the cadmium acetate dihydrate is 1:(9 - 90).
6. The method according to claim 1, characterized in that, the volume ratio of the deionized water to the dimethylformamide is 1:
6.
7. The method according to claim 1, characterized in that, the mass ratio between the cadmium acetate dihydrate and the thiourea is 3:
5.
8. A covalent organic framework compound / cadmium sulfide composite photocatalyst manufactured by the method according to any one of claims 1 - 7.
9. Application of the covalent organic framework compound / cadmium sulfide composite photocatalyst according to claim 8 in photocatalytic hydrogen evolution.